2019
DOI: 10.15561/18189172.2019.0203
|View full text |Cite
|
Sign up to set email alerts
|

Empirical verification of self-rated positive health (somatic dimension) in women with professional competence in the field of health education

Abstract: Purpose: to address a question whether reports of young women concerning their positive health are concordant with indices based on recommended methods of measuring health? Material: the study consist of fifteen, 23 years old female students of physiotherapy (height: QUOTE 15X"> =164.3 ±4.55; weight: QUOTE 15X"> = 60.7 ±6.76) who declared engagement in everyday or occasional physical activity. They completed The profile of the sense of positive health and survival abilities indices (SPHSA questionnaire).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(22 reference statements)
2
0
0
Order By: Relevance
“…Interesting phenomena, regarding possible future development of such study lies in comparing subjective and objective indicators of health. Self-reported estimation of some health indices could be compared to objective, tested by fitness test evaluation (Dobosz, 2018). In mentioned study, males results was not statistically significant, while newer study of same phenomena about female athletes shown significant correlation between subjective and objective measurements (Dobosz, 2019).This is concurrent with our obtained results, where females results have higher correlation between self-reported general indicator and more objective detailed evaluation.…”
Section: Sd -Standard Deviationsupporting
confidence: 77%
See 1 more Smart Citation
“…Interesting phenomena, regarding possible future development of such study lies in comparing subjective and objective indicators of health. Self-reported estimation of some health indices could be compared to objective, tested by fitness test evaluation (Dobosz, 2018). In mentioned study, males results was not statistically significant, while newer study of same phenomena about female athletes shown significant correlation between subjective and objective measurements (Dobosz, 2019).This is concurrent with our obtained results, where females results have higher correlation between self-reported general indicator and more objective detailed evaluation.…”
Section: Sd -Standard Deviationsupporting
confidence: 77%
“…Self-reported estimation of some health indices could be compared to objective, tested by fitness test evaluation (Dobosz, 2018). In mentioned study, males results was not statistically significant, while newer study of same phenomena about female athletes shown significant correlation between subjective and objective measurements (Dobosz, 2019).This is concurrent with our obtained results, where females results have higher correlation between self-reported general indicator and more objective detailed evaluation. In light of the results acquired, it would seem to be even more justifiable to continue research on the subject of the circumstances of shaping the responsibility for undertaking behavioural traits that have an impact on health.…”
Section: Sd -Standard Deviationsupporting
confidence: 77%